Tongue Force Training Induces Plasticity of the Lingual Motor Cortex in Young Adult and Aged Rats - Cullins, Miranda J.; Wenninger, Julie M.; Cullen, Jared S.; Russell, John A.; Kleim, Jeffrey A.; Connor, Nadine P. (Frontiers in Neuroscience, 2019)
Tongue exercise programs are used clinically for dysphagia in aged individuals and have been shown to improve lingual strength. However, the neural mechanisms of age-related decline in swallowing function and its association with lingual strength are not well understood. Using an established rat model of aging and tongue exercise, we hypothesized that the motor cortex of aged rats would have a smaller lingual motor map area than young adult rats and would increase in size as a function of tongue exercise. Over 8 weeks, rats either underwent a progressive resistance tongue exercise program (TE), learned the task but did not exercise (trained controls, TC), or were naïve untrained controls (UC). Cortical motor map areas for tongue and jaw were determined using intracortical microstimulation. Rats in the TE and TC groups had a significantly larger motor cortex region for the tongue than the UC group. Lingual cortical motor area was not correlated with protrusive tongue force gains and did not differ significantly with age. These results suggest that learning a novel tongue force skill was sufficient to induce plasticity of the lingual motor cortex yet increasing tongue strength with progressive resistance exercise did not significantly expand the lingual motor area beyond the gains that occurred through the skilled learning component.